2019
DOI: 10.1101/718213
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gut microbiome shifts with urbanization and potentially facilitates a zoonotic pathogen in a wading bird

Abstract: 24Microbial communities in the gastrointestinal tract influence many aspects of host health, 25 including metabolism and susceptibility to pathogen colonization. These relationships and the 26 environmental and individual factors that drive them are relatively unexplored for free-living 27 wildlife. We quantified the relationships between urban habitat use, diet, and age with 28 microbiome composition and diversity for 82 American white ibises (Eudocimus albus) captured 29 along an urban gradient in south F… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 72 publications
(43 reference statements)
0
13
0
Order By: Relevance
“…At the same time, increases in site fidelity and decreases in movement can increase the size of epidemics in urban areas, particularly if urban sites accumulate high numbers of susceptible hosts [ 4 ]. Ibis sampled at urban sites have significantly higher prevalence of enteric Salmonella [ 43 ] and differences in their bacterial microbiome compared to ibis at natural sites [ 44 ], indicating that species interactions and pathogen transmission differ between urban and natural sites (see also [ 45 ]). The presence of generalist individuals in the population could maintain pathogen dispersal [ 80 , 81 ], but the importance of highly mobile individuals for infection dynamics depends on both their abundance and the relative rates of movement and recovery [ 82 ], so the impact of generalists could be limited if they are much less common than habitat specialists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, increases in site fidelity and decreases in movement can increase the size of epidemics in urban areas, particularly if urban sites accumulate high numbers of susceptible hosts [ 4 ]. Ibis sampled at urban sites have significantly higher prevalence of enteric Salmonella [ 43 ] and differences in their bacterial microbiome compared to ibis at natural sites [ 44 ], indicating that species interactions and pathogen transmission differ between urban and natural sites (see also [ 45 ]). The presence of generalist individuals in the population could maintain pathogen dispersal [ 80 , 81 ], but the importance of highly mobile individuals for infection dynamics depends on both their abundance and the relative rates of movement and recovery [ 82 ], so the impact of generalists could be limited if they are much less common than habitat specialists.…”
Section: Discussionmentioning
confidence: 99%
“…Many ibis now forage in city parks, where they feed on human-provided resources (including bread) and show higher site fidelity, returning to the same parks over weeks or months [ 41 , 42 ]. Past work in this system showed that ibis can be infected by generalist enteric pathogens such as Salmonella, for which infection prevalence is highest in urban flocks [ 43 , 44 ]. Ibis might contribute to Salmonella transmission, or their exposure could reflect transmission from other reservoir species or environmental sources [ 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…The combination of human‐induced habitat changes and novel biotic interactions produces divergent fitness landscapes that promote specific phenotypic traits in cities (Alberti et al., 2017; Ouyang et al., 2018). Urban wildlife exhibit increased nocturnality (Gaynor et al., 2018), cognitive and problem‐solving innovations (Audet et al., 2016; Snell‐Rood & Wick, 2013), heightened tolerance and habituation (Lowry et al., 2013; Sol et al., 2013), and dietary niche shifts (Murray, Lankau, et al, 2020; Pagani‐Núñez et al., 2019), all of which facilitate survival and reproductive success in cities. Phenotypic shifts and plasticity in urban contexts can promote local adaptation by reducing the likelihood of human–wildlife encounters (Ditchkoff et al., 2006; Tuomainen & Candolin, 2011).…”
Section: Ecological Drivers Of Conflict and Associated Biological Outmentioning
confidence: 99%
“…At the ‘anthropogenic’ end of the urban spectrum, microbial communities existing within a restricted host niche would be expected to be of lower diversity, while facing higher selection pressures. A recent study conducted on American white ibises ( Eudocimus albus ) demonstrated that microbial diversity was lost along a gradient of urbanization, which correlated with higher shedding of pathogenic Salmonella—suggesting that urbanization could lead to microbial perturbations that favour pathogen colonization (Murray et al., 2020). Here, we also hypothesize that microbial communities are increasingly divergent than those present at other household interfaces, as the compositional distinctness of host assemblages (measured as LCBD indices) increases.…”
Section: Discussionmentioning
confidence: 99%